PENGEMBANGAN SOAL OPEN ENDED PADA POKOK BAHASAN PYTHAGORAS - Syutaridho Syutaridho (Program Studi Pendidikan Matematika UIN Raden Fatah Palembang, 2015)
Logical and creative thinking is the point in the national education goals and purposes of learning mathematics in general. Open ended is one alternative in achieving these goals, which open ended present a problem in terms of solving problems that have more than one strategy, so as to give an opportunity to the students to think logically and creatively. The purpose of this research is generating open-ended questions are valid, practical and determine potential effects on student learning outcomes. The focus of this research is the development of a matter through four stages, namely self evaluation, expert reviews and one-to-one, small group, and a field test. The collection of data is done in a way, test and analysis documentation of students' answers. The test results obtained during tests filed an average of 74.125 where the learning outcomes, the average value are classified in either category. The conclusion of this study are 1) learning tools developed in this study considered a valid and practical; 2) The achievement of student learning outcomes are seen from the results of field tests with an average of 74.125, where average values are classified in either category